Aproximació a l'obra de mossén Vicent Manuel Branchat: Pesa chiqueta en un acte. - TORTAJADA, ROBERT MARCH (Scripta, 2023)
The aim of this article is to think about the figure of Vicent Manuel Branchat, priest and author of the early 19th century works. Thus, we review the previous studies that researchers and specialists have devoted to it, starting from the edition of Pesa chiqueta en un acte, edited by Joan Fuster and published in La decadència al País Valencià. In addition, we think of Branchat as a pre-Renaissance author in order to place him at the crossroads between the col·loqui and the sainet.